Happiness and Mental Illness: Virtue ethics in Dialogue with Psychology. (27th December 2018) - Clifton, Shane; Stevens, Bruce
Abstract : This interdisciplinary article explores the intersection between the virtue ethics tradition and psychological therapies exploring the meaning of happiness for people living with a disabling mental illness. The logic of virtue ethics faces the challenge of mental illness, which is how to conceive of eudaimonia in the context of an illfness that targets happiness and potentially disrupts a person's capacity to function rationally and exercise virtue. Drawing on two illustrative case studies of schizophrenia and major depression disorder, this article identifies substantive points of contact between virtue ethics and the therapeutic strategies of recovery theory and Acceptance and Commitment Therapy. In so doing, it aims to provide ways of thinking about happiness that can help therapists and people with a mental illness conceive of flourishing, not despite mental illness, but by incorporating the experience into the storied meaning of life. And since mental illness reflects the vulnerabilities that are central to human life, its examination also expands the horizons of the virtue ethics tradition.